Photoinduced Electron Transfer in Organic Solar Cells. Issue 2 (8th February 2016) - Song, Peng; Li, Yuanzuo; Ma, Fengcai; Pullerits, Tõnu; Sun, Mengtao
Abstract: Electron transfer (ET) is the key process in light‐driven charge separation reactions in organic solar cells. The current review summarizes the progress in theoretical modelling of ET in these materials. First we give an account of ET, with a description originating from Marcus theory. We systematically go through all the relevant parameters and show how they depend on different material properties, and discuss the consequences such dependencies have for the performance of the devices. Finally, we present a set of visualization methods which have proven to be very useful in analyzing the elementary processes in absorption and charge separation events. Such visualization tools help us to understand the properties of the photochemical and photobiological systems in solar cells. Abstract : Photoinduced electron transfer in organic solar cells : Electron transfer (ET) is the key process in light‐driven charge separation reactions in organic solar cells. The current review summarizes the progress in the theoretical modelling of ET in OSCs, while there is still much to be understood on the role and influence of external circumstances on power conversion efficiencies of OPV materials.